Aplikasi Android Pendaftaran Pengurusan Akta Jual Beli Berbasis Android - Siti Saadah; Ahmad Fikri Zulfikar (CV. Multi Kreasi Media, 2023)
PT Bumi Serpong Damai is a company engaged in real estate development activities. The company has developed a new city, which is a planned and integrated residential area, with facilities/infrastructure, environmental facilities and parks, called BSD City. In the registration process, the sale/purchase deed is currently still done manually, which causes the registration process to have many errors and take a longer time. Along with the development of increasingly advanced technology, an online registration system is needed to simplify the registration process and prevent errors from occurring. The registration application for the sale/purchase deed consists of web and android applications. The android application is used by the applicant or user to register and the web application is used by the legal staff to manage data that has registered online.